Peer-Assisted Content Delivery to Reduce the Bandwidth of TSTV Service in IPTV System - El Hassane Khabbiza; Rachid El Alami; Hassan Qjidaa (International Journal of Digital Multimedia Broadcasting)
With great technologies, emerge new needs and requirements. The progress achieved in Access broadband rates accentuated the demand on IPTV (Internet Protocol Television) services specially Video on Demand (VOD) and Time Shift TV (TSTV) which led subsequently to a great need for efficiency in the use of bandwidth consumed by those services. Optimization solutions are considered by IPTV service providers to lighten the service load especially on Access Nodes uplinks. This paper describes an optimization of TSTV dedicated bandwidth based on a peer-assisting TSTV content delivery, a solution in which the users STBs (set-top-boxes) assist the central TSTV servers in the service fulfillment. For this purpose, for each TSTV request, the STB will be receiving the TSTV stream from a neighbor STB instead of the central server. By using this method, the unicast traffic will not pass through the IP network; it will be a peer-to-peer communication within the access network. Extensive simulation results were included to illustrate the validity of the proposed new solution.